Intergenerational transfers and the intergenerational transmission of poverty in Bangladesh: Preliminary results from a longitudinal study of rural households - Quisumbing, Agnes R. (Chronic Poverty Research Centre, 2008)
This paper examines the determinants of intergenerational transfers and the association between such transfers and the intergenerational transmission of poverty, based on a new longitudinal dataset from Bangladesh. Women receive less schooling, land and inherited assets than men, and also give up their inheritance to their brothers in exchange for economic and social support. While intergenerationally transferred assets, mostly controlled by the husband, increase levels of current assets and consumption, only husbands’ schooling and inherited land, as well as women’s social networks, are protective against chronic poverty. - from summary text